The Social Competence of Al-Qur’an Hadith Teachers and the Learning Motivation of Seventh Grade Students at Madrasah Tsanawiyah - Nurjamilah Indah Lestari; Ismail Ismail; Fitriani Fitriani; Rosika Indri Karadona (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to examine the implementation of the social competence of Qur’an and Hadith teachers in optimizing the learning motivation of seventh-grade students at Madrasah Tsanawiyah Radhiatul Adawiyah Mangga Tiga Makassar. Methodology: This research employs a descriptive qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews, and documentation, with participants consisting of Qur’an and Hadith teachers and seventh-grade students. Main Findings: The findings reveal that teachers’ social competence significantly enhances students’ learning motivation. Teachers demonstrated strong social skills through openness, fairness, effective communication, and the ability to foster harmonious relationships with students and the school environment. This competence was implemented through enjoyable teaching methods, the use of diverse learning media, and teachers’ active involvement in stimulating students’ enthusiasm for learning. Supporting factors included teacher collaboration and a familial approach, while inhibiting factors comprised students’ low discipline, limited school facilities, lack of specialized training for teachers, and students’ weak foundational abilities. Novelty/Originality of this study: The originality of this research lies in its specific focus on Qur’an and Hadith teachers at Madrasah Tsanawiyah Radhiatul Adawiyah Mangga Tiga Makassar, offering new insights into the role of teachers’ social competence as an effective strategy to enhance students’ learning motivation in Islamic secondary education. This study emphasizes the importance of teachers’ social competence in creating a positive learning atmosphere and fostering active student participation.